Release of metal ions from round and rectangular NiTi wires - Arash Azizi; Abdolreza Jamilian; Francesca Nucci; Zinat Kamali; Nima Hosseinikhoo; Letizia Perillo (SpringerOpen, 2016)
Abstract Background The aim of this study was to evaluate the amount of nickel and titanium ions released from two wires with different shapes and a similar surface area. Methods Forty round nickel-titanium (NiTi) arch wires with the diameter of 0.020 in. and 40 rectangular NiTi arch wires with the diameter of 0.016 × 0.016 in. were immersed in artificial saliva during a 21-day period. The surface area of both wires was 0.44 in.2. Wires were separately dipped into polypropylene tubes containing 50 ml of buffer solution and were incubated and maintained at 37 °C. Inductively coupled plasma atomic emission spectrometry (ICP-AES) was used to measure the amount of ions released after exposure lengths of 1 h, 24 h, 1 week, and 3 weeks. Repeated measures ANOVA and Tukey tests were used to evaluate the data. Results The results indicated that the amount of nickel and titanium concentrations was significantly higher in the rectangular wire group. The most significant release of all metals was measured after the first hour of immersion. In the rectangular wire group, 243 ± 4.2 ng/ml of nickel was released after 1 h, while 221.4 ± 1.7 ng/ml of nickel was released in the round wire group. Similarly, 243.3 ± 2.8 ng/ml of titanium was released in the rectangular wire group and a significantly lower amount of 211.9 ± 2.3 ng/ml of titanium was released in the round wire group. Conclusions Release of metal ions was influenced by the shape of the wire and increase of time.